Detection of infectious bronchitis virus in experimentally infected chickens by an antigen-competitive ELISA - Bronzoni, R. V. M. [UNESP]; Pinto, A. A. [UNESP]; Montassier, H. J. [UNESP] (Taylor & Francis, 2001)
An antigen-competitive enzyme-linked immunosorbent assay (Ag-C-ELISA) was developed for the detection of infectious bronchitis virus (IBV) antigens, M41 strain, in tissues from experimentally infected chickens, or in allantoic fluid harvested from inoculated embryonated eggs. The detection limit of IBV in the Ag-C-ELISA was 104.1 median embryo infective doses (EID50)/well. Tracheal and lung samples from chickens vaccinated with 102.5 EID50 of live attenuated infectious bronchitis (H120) vaccine were negative in the direct detection Ag-C-ELISA. The results indicate that the Ag-C-ELISA has the potential to detect IBV, either directly in tissue samples or when combined with the passage of material in embryonated eggs, thereby constituting an alternative method for the diagnosis of IBV.
Keywords: allantoin; chicken; enzyme linked immunosorbent assay; genetic strain; infectious bronchitis virus; inoculation; virus antigen; virus detection; virus vaccine; Aves; Avian infectious bronchitis virus; Gallus gallus